2009
DOI: 10.1007/s12253-009-9170-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Ki-67 and Sex Steroid Hormone Receptors Between Genders in Peritoneal Mesothelioma

Abstract: Gender influence on survival in mesothelioma has been observed in several large clinical series. However, this gender effect has not been investigated. Female patients often have less aggressive tumors and survive longer. However, few studies in the literature have explained the molecular basis of this finding. Understanding this difference at a molecular level may offer the hope of improving survival via hormonal manipulation.We investigate the expression of Ki-67 and sex steroid receptors; estrogen receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…This seeming discrepancy may be due to different types of exposure to the carcinogen. Recently, sex steroid receptors have been found in peritoneal mesothelioma (76).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…This seeming discrepancy may be due to different types of exposure to the carcinogen. Recently, sex steroid receptors have been found in peritoneal mesothelioma (76).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…MIB-1 index of diffuse peritoneal mesothelioma is reported to range from 0.6% to 10%. [10][11][12] MIB-1 index higher than cutoff level in diffuse peritoneal mesothelioma correlates with poor outcome. In contrast, MIB-1 indices were low in the present 9 cases, These results may indicate that MCPM has malignant potential with low proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining with Ki-67 of Mib-1 antibodies is an excellent marker of cellular proliferation and tumour aggressiveness. [30] Three independent studies showed low Ki-67 expression in peritoneal mesothelioma, with a median of 0.6% to 10% positive cells. (13,(29)(30)).…”
Section: Patho-biological Featuresmentioning
confidence: 98%
“…[30] Three independent studies showed low Ki-67 expression in peritoneal mesothelioma, with a median of 0.6% to 10% positive cells. (13,(29)(30)). Analogously, mitotic rate is gerally low in malignant peritoneal mesothelioma, but higher proliferative activity correlates with poor outcome.…”
Section: Patho-biological Featuresmentioning
confidence: 98%